2013
DOI: 10.1021/nn404015y
|View full text |Cite
|
Sign up to set email alerts
|

Realizing High-Efficiency Omnidirectional n-Type Si Solar Cells via the Hierarchical Architecture Concept with Radial Junctions

Abstract: Hierarchical structures combining micropyramids and nanowires with appropriate control of surface carrier recombination represent a class of architectures for radial p-n junction solar cells that synergizes the advantageous features including excellent broad-band, omnidirectional light-harvesting and efficient separation/collection of photoexcited carriers. The heterojunction solar cells fabricated with hierarchical structures exhibit the efficiency of 15.14% using cost-effective as-cut Czochralski n-type Si s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
86
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 96 publications
(87 citation statements)
references
References 46 publications
0
86
1
Order By: Relevance
“…4C shows the wavelength (λ)-dependent external quantum yield (Φ ext ) for HTJ-SijNiO x , n-CdTejNiO x , and a-Si:HjNiO x photoelectrodes maintained potentiostatically at 1.93 V vs. RHE, at which the light-limited current density was produced. The quantum yields of the HTJ-SijNiO x structure were higher than the values reported for analogous HTJ-Si-based solid-state devices (39). The higher value of Φ ext can be ascribed primarily to the antireflective behavior and broadband suppression of reflection by the NiO x film on the textured HTJ-Si surface maintained under working conditions.…”
Section: Figurementioning
confidence: 63%
See 2 more Smart Citations
“…4C shows the wavelength (λ)-dependent external quantum yield (Φ ext ) for HTJ-SijNiO x , n-CdTejNiO x , and a-Si:HjNiO x photoelectrodes maintained potentiostatically at 1.93 V vs. RHE, at which the light-limited current density was produced. The quantum yields of the HTJ-SijNiO x structure were higher than the values reported for analogous HTJ-Si-based solid-state devices (39). The higher value of Φ ext can be ascribed primarily to the antireflective behavior and broadband suppression of reflection by the NiO x film on the textured HTJ-Si surface maintained under working conditions.…”
Section: Figurementioning
confidence: 63%
“…The higher value of Φ ext can be ascribed primarily to the antireflective behavior and broadband suppression of reflection by the NiO x film on the textured HTJ-Si surface maintained under working conditions. The decrease in Φ ext at low and high wavelengths, respectively, was primarily attributable to recombination at the textured front and back interfaces between the crystalline Si and the a-Si surface passivation layer (39). The low blue response was also associated with absorption by the a-Si heterogeneous coating.…”
Section: Figurementioning
confidence: 93%
See 1 more Smart Citation
“…14 carrier lifetimes (up to the millisecond range), no light-induced degradation caused by boron-oxygen pair, and high impurity tolerance. [16][17][18][19][20][21] Despite the great success in developing high performance SHJ devices, a large number of photons are still wasted, leading to the significant power loss. It is reported that the total power loss is more than 20% of the current output power.…”
mentioning
confidence: 99%
“…Furthermore, a hierarchical structure combining micropyramids and nanowires has been reported for enhanced light-trapping [23, 24]. Nevertheless, little is known about decreasing the reflection of micropillars or that of low-reflective b-Si having a low surface area.…”
Section: Introductionmentioning
confidence: 99%